Revealing the Symbolic Meaning of Heri Dono's Flying Angels: From Paul Ricoeur's Hermeneutic Perspective - Sumarwahyudi Sumarwahyudi (Gondang: Jurnal Seni dan Budaya, 2025)
Flying Angels (1996) by Heri Dono is examined in this article as a visual installation rich in symbolic complexity and interpretive openness. This work is selected as the object of study to explore how Paul Ricoeur’s hermeneutic framework can be applied to reveal the layered meanings embedded in contemporary visual art. Employing a qualitative descriptive method grounded in Ricoeur’s textual hermeneutics, the research positions the artwork as an autonomous visual discourse that generates meaning beyond the artist’s original intention. The analysis focuses on visual, symbolic, and narrative elements, particularly the representation of angelic figures rendered grotesque, mechanical, and ironic. Through hermeneutic interpretation, these angels—traditionally associated with purity, transcendence, and moral authority—are understood as ambivalent symbols that articulate tensions between spirituality, technology, and social critique within modernity. The mechanical movements, hybrid materials, and vivid colours operate as a symbolic system reflecting the distortion of spiritual values under technological rationality and globalised cultural conditions. The findings demonstrate that Flying Angels functions not merely as an aesthetic installation, but as an open visual text that invites critical reflection on the erosion of spirituality, processes of dehumanisation, and the transformation of traditional values in the technological era. By emphasising Ricoeur’s concepts of distanciation, surplus of meaning, and dialogical interpretation, this study contributes to Indonesian contemporary art discourse and underscores the relevance of hermeneutic approaches in expanding interpretive dialogue across cultural and temporal contexts.